Polystyrene Sulfonate Threaded through a Metal–Organic Framework Membrane for Fast and Selective Lithium‐Ion Separation. (31st October 2016) - Guo, Yi; Ying, Yulong; Mao, Yiyin; Peng, Xinsheng; Chen, Banglin
Abstract: Extraction of lithium ions from salt‐lake brines is very important to produce lithium compounds. Herein, we report a new approach to construct polystyrene sulfonate (PSS) threaded HKUST‐1 metal–organic framework (MOF) membranes through an in situ confinement conversion process. The resulting membrane PSS@HKUST‐1‐6.7, with unique anchored three‐dimensional sulfonate networks, shows a very high Li + conductivity of 5.53×10 −4  S cm −1 at 25 °C, 1.89×10 −3  S cm −1 at 70 °C, and Li + flux of 6.75 mol m −2  h −1, which are five orders higher than that of the pristine HKUST‐1 membrane. Attributed to the different size sieving effects and the affinity differences of the Li +, Na +, K +, and Mg 2+ ions to the sulfonate groups, the PSS@HKUST‐1‐6.7 membrane exhibits ideal selectivities of 78, 99, and 10296 for Li + /Na +, Li + /K +, Li + /Mg 2+ and real binary ion selectivities of 35, 67, and 1815, respectively, the highest ever reported among ionic conductors and Li + extraction membranes.